Implementation of Prototype Method in a Web-Based Educational Word Guessing Game with Melodic Elements - Gunawan Prayitno; Yuspin Yokbet Danomira (Yayasan Cita Cendekiawan Al Khwarizmi, 2026)
The rapid development of digital technology has encouraged the use of interactive learning media, particularly web-based educational games, to support engaging learning experiences. This study aims to design, implement, and evaluate a web-based educational word guessing game integrated with melodic elements as an alternative digital learning medium. The study employs the prototype development method, which enables iterative system development through continuous user feedback. The research stages include needs analysis, prototype design, system development, and system testing and evaluation. System evaluation was conducted through functional testing using a black-box approach to ensure that all features operated according to predefined requirements, as well as descriptive usability evaluation to assess ease of use and user interaction. The results indicate that the developed system functions properly, with core features such as word guessing mechanics, score management, and melodic feedback operating as intended. The usability evaluation shows that the game interface is easy to understand and provides a clear gameplay flow for users. These findings suggest that the developed web-based educational word guessing game has the potential to serve as an interactive and engaging digital learning medium. This study contributes to the development of educational games by demonstrating the application of the prototype method and the integration of melodic elements to enhance user interaction in web-based learning environments.